Joint Inversion Algorithm of Sea Surface Temperature From Microwave and Infrared Brightness Temperature - Chen, Zhiwei; Jin, Rong; Li, Qingxia; Zhao, Guanghui; Xiao, Chengwang; Lei, Zhenyu; Huang, Yuhang (IEEE transactions on geoscience and remote sensing, 2022)
The demand for high-precision sea surface temperature (SST) has been growing rapidly in recent years because SST is one of the key parameters to describe the thermal state of the sea surface. This article analyzes the differences between microwave remote sensing and infrared remote sensing for SST, including the spatial resolution difference and the penetration depth difference. In order to improve the accuracy of retrieved SST, this article proposes a joint inversion algorithm for SST from combining microwave brightness temperature (BT) and infrared BT, which has also taken the influence of wind speed and atmosphere into consideration. Experiments confirm that SST data obtained from the joint inversion algorithm are more accurate than those obtained from the existing inversion algorithms.